2020
DOI: 10.1103/physrevd.101.044058
|View full text |Cite
|
Sign up to set email alerts
|

Viability of bouncing cosmology in energy-momentum-squared gravity

Abstract: We analyze the early-time isotropic cosmology in the so-called Energy-Momentum Squared Gravity (EMSG). In this theory, a T µν T µν term is added to the Einstein-Hilbert action, which has been shown to replace the initial singularity by a regular bounce. We show that this is not the case, and the bouncing solution obtained does not describe our universe since it belongs to a different solution branch. The solution branch that corresponds to our universe, while non-singular, is geodesically incomplete. We analyz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 34 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…It has been shown in [18] that EMSG has a bouncing solution preventing the early Universe singularity. However, recently in [20] the viability of this bouncing solution has been doubted. EMSG in the Palatini formulation has been investigated in [21].…”
Section: Standard Formulation Of Emsgmentioning
confidence: 99%
“…It has been shown in [18] that EMSG has a bouncing solution preventing the early Universe singularity. However, recently in [20] the viability of this bouncing solution has been doubted. EMSG in the Palatini formulation has been investigated in [21].…”
Section: Standard Formulation Of Emsgmentioning
confidence: 99%
“…Shabani and Ziaie [28] have studied the classical bouncing solutions in FRW background and Tripathy et al [29] have presented the bouncing solution with exponential and power law cosmology. Barbar et al [30] have analyzed the viability of bouncing cosmology by incorporating the square of energy momentum tensor. Wu et al [31] have obtained the generalized Friedmann equations and studied its cosmological implications.…”
Section: ∂Tmentioning
confidence: 99%
“…Bahamonde et al [19] investigated the minimal and nonminimal coupling models of EMSG and observed that these models describe the current cosmic accelerated expansion. ere has been a recent literature [20][21][22] that indicates various cosmological applications of this modified theory. It is evident from the above set of literature that EMSG requires more focus, and hence motivations to analyze such theory are very high.…”
Section: Introductionmentioning
confidence: 99%